Bahasa Gaul Dan Media Sosial: Tinjauan Literatur Tentang Perubahan Struktur Dan Makna - Anita Candra Dewi (Prodi PGSD Unsultra, 2025)
The development of communication technology, especially social media, has brought significant changes in the use of language, including slang. Slang, which initially developed in limited communities, is now spreading rapidly through various digital platforms. This study aims to examine changes in the structure and meaning of slang in social media based on a literature review. The results of the study show that slang has undergone morphological, syntactic, and semantic modifications influenced by user creativity and the need for faster and more efficient communication. In addition, social media is a catalyst in the spread and normalization of the use of slang in formal and informal communication. This study also discusses the impact of slang on the language of the younger generation and its implications for the development of the Indonesian language. This study is expected to provide insight for academics, educators, and language observers in understanding the dynamics of slang in the digital era